Uwarunkowania kulturowe procesów integracji w regionie Azji i Pacyfiku – perspektywa biznesu międzynarodowego - Rozkwitalska, Małgorzata (Cultural determinants of the integration process in the Asia-Pacific Region – the international business perspective, 2009)
The economic integration processes take place in different parts of the world. States of the Asia- Pacific region made also an effort to integrate structures of their economies. Cultural dimension is - besides political, legal, and economic factors - an important determinant of co-operation between countries in international business. Cultural environment influences choices and behaviour of various market entities. In this thesis an effort was made to distinguish cultural barriers of integration in the APEC region. It was emphasized that these barriers showed up in artifacts, norms and values, and basic assumptions. According to the analysis, there can be found two blocks in the APEC region: the relatively homogenous block of Anglo-Saxon countries, and more diversified block of collectivistic, high power distance countries, that is created by all remaining group of states. There was also described the attitude of APEC influencers towards cultural diversity, and selected APEC’s initiatives aimed to spread cultural awareness and lessening cultural barriers
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 67, s. 152-164